First survey of mammography practice in sudan: Radiation exposure and setting national diagnostic reference levels. (September 2016) - Suliman, I.I.; Awad, S.; Mahdi, Alaa; Ahmed, N.
Abstract : Introduction: Radiation dose in mammography is evaluated in terms of the Mean glandular dose (MGD) because the glandular tissues are believed to be the most sensitive to radiation-induced carcinogenesis. Purpose: The purpose of this study was to estimate mean glandular dose levels (DG) in six mammography systems in Khartoum, Sudan, and to propose national diagnostic reference in Sudan. Materials and methods: Doses were estimated in terms of the Mean Glandular Dose (MGD) in 400 examinations in 204 women who underwent Cranio-Caudal (CC) and Medio-Lateral oblique (MLO) mammography in seven clinics in Khartoum state, Sudan. incident air kerma (IAK) was first estimated from X-ray tube output measurements and patient exposure factors. MGD was then estimated from IAK using conversion coefficients that a count for breasts glandularity and the difference in the X-ray spectrum used. Results: The mean MGD for CC and MLO was (4.45 ± 2.2) mGy and (4.15 ± 2.1) mGy, respectively. The MGD per image was (4.3 ± 1.15) mGy and the MGD per woman was (8.6 ± 2.22) mGy. The MGD values were compared with results from the literature. Significant variations in MGD were observed and revealed important considerations for dose optimization and will be used for setting national diagnostic reference levels. Conclusion: The study offered the first projection of radiation exposure in X-ray mammography in Sudan and thus offered the opportunity for dose optimization and setting national diagnostic reference levels. Disclosure: Authors do not have any relationship that may bias their presentation.